2014
DOI: 10.1111/cmi.12391
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia pestistargets neutrophils via complement receptor 3

Abstract: Yersinia species display a tropism for lymphoid tissues during infection, and the bacteria select innate immune cells for delivery of cytotoxic effectors by the type III secretion system. Yet the mechanism for target cell selection remains a mystery. Here we investigate the interaction of Yersinia pestis with murine splenocytes to identify factors that participate in the targeting process. We find that interactions with primary immune cells rely on multiple factors. First, the bacterial adhesin Ail is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 92 publications
0
17
0
1
Order By: Relevance
“…For example, contact between the Y. pseudotuberculosis adhesive protein invasin and β1 integrin receptor on neutrophils induces extrusion of microbicidal DNA, via NETosis, a processes that is inhibited by effectors delivered by the T3SS (Figure 1A) [23]. In addition to stimulating host immune responses, adhesion of yersiniae to host cells facilitates Yop effector translocation by the T3SS into immune cells during infection, while factors in serum can restrict levels of translocation by shifting the specificity of Yop targeting [2426]. Additional bacterial factors are important for fine-tuning effector translocation.…”
Section: Later Interactions Of Yersinia With Host Cells-important Formentioning
confidence: 99%
“…For example, contact between the Y. pseudotuberculosis adhesive protein invasin and β1 integrin receptor on neutrophils induces extrusion of microbicidal DNA, via NETosis, a processes that is inhibited by effectors delivered by the T3SS (Figure 1A) [23]. In addition to stimulating host immune responses, adhesion of yersiniae to host cells facilitates Yop effector translocation by the T3SS into immune cells during infection, while factors in serum can restrict levels of translocation by shifting the specificity of Yop targeting [2426]. Additional bacterial factors are important for fine-tuning effector translocation.…”
Section: Later Interactions Of Yersinia With Host Cells-important Formentioning
confidence: 99%
“…Our assays detect factor H binding at high concentrations of Y. pestis , which may indicate that Ail‐dependent recruitment of factor H in buboes may prevent production of the alarmones, C3a and C5a, thus preventing PMN infiltration. Alternatively, it is possible that the lack of PMN recruitment seen during bubonic plague models of infection are due to a reduced efficiency of Yop delivery via T3SS in a Δ ail mutant (Marketon et al ., ; Merritt et al ., ). Nonetheless, our studies show Y. pestis can survive complement‐mediated lysis in human serum, even without the ability to recruit factor H or vitronectin (as demonstrated by Ail‐F80A/F130A).…”
Section: Discussionmentioning
confidence: 97%
“…While recent studies have indicated that Ail influences in vivo target cell selection for Yop delivery during Yersinia infections (33)(34)(35), the mechanism(s) by which Ail directs cell targeting of Yop secretion is unclear. Ail could recruit ECM components to direct Yop delivery to specific immune cells with receptors for those components to disarm the host immune response.…”
Section: Discussionmentioning
confidence: 99%